The Importance of Nutrition Education to Change Mother's Knowledge and Behaviour in Achieving Adequate Nutrition for Toddler - Fitriyani, Poppy; Mulyono, Sigit; Handayani, Tri Widyastuti (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
The problem of undernutrition among toddlers is still a problem that cannot be resolved properly. The role of the family in overcoming the problem of undernutrition is very necessary because toddlers are dependent on nutritional requirements. Therefore, efforts are needed to overcome this problem by increasing the provision of appropriate nutritional education for toddlers so that toddlers avoid the problem of malnutrition. This research aims to determine the extent of the influence of providing nutrition education on mothers' knowledge and behavior in fulfilling nutrition for toddlers. The research design used a "Quasi experimental pre-post test design with control" design with 37 respondents in the intervention group and 37 control groups. This research was carried out by providing intervention to 37 families of toddlers, especially education about toddler nutrition and looking at the effect on changes in mothers' knowledge and behavior in fulfilling toddler nutrition. The nutrition education intervention was provided over 4 meetings and continued with assistance through home visits over 2 meetings. The results of the research show that there is an influence between providing nutrition education on family knowledge and behavior. This data can be used as material for consideration by community nurses in providing education about nutrition in an effort to increase mothers' knowledge and behavior in fulfilling nutrition for toddlers to avoid malnutrition problems.